The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1017/s0033291713000196
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia genetic variants are not associated with intelligence

Abstract: Background Schizophrenia is associated with lower pre-morbid intelligence (IQ) in addition to (pre-morbid) cognitive decline. Both schizophrenia and IQ are highly heritable traits. Therefore, we hypothesized that genetic variants associated with schizophrenia, including copy number variants (CNVs) and a polygenic schizophrenia (risk) score (PSS), may influence intelligence. Method IQ was estimated with the Wechsler Adult Intelligence Scale (WAIS). CNVs were determined from single nucleotide polymorphism (SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 28 publications
3
41
0
1
Order By: Relevance
“…To our knowledge such studies have not yet been conducted. But proof of concept can be seen in two recent studies showing that genetic risks discovered in GWAS of schizophrenia are related to cognitive ability and cognitive decline (McIntosh et al 2013; Lencz et al 2014), although this finding remains contentious (van Scheltinga et al 2013). …”
Section: Genetic Risk Scores In Social Science Research: 3 Suggestionsmentioning
confidence: 99%
“…To our knowledge such studies have not yet been conducted. But proof of concept can be seen in two recent studies showing that genetic risks discovered in GWAS of schizophrenia are related to cognitive ability and cognitive decline (McIntosh et al 2013; Lencz et al 2014), although this finding remains contentious (van Scheltinga et al 2013). …”
Section: Genetic Risk Scores In Social Science Research: 3 Suggestionsmentioning
confidence: 99%
“…It has also been used to differentiate genetically, for example, schizophrenia and autism (Vorstman et al, 2013) or schizophrenia and intelligence (van Scheltinga et al, 2013). The schizophrenia PRS has been correlated with quantitative measures of psychosis in terms of symptoms scales (Derks et al, 2012) and neuroimaging measures (Walton et al, 2013).…”
Section: Polygenic Scoresmentioning
confidence: 99%
“…A further study by the same group [6] found no link between total deletion burden and intelligence as measured by the Wechsler Adult Intelligence Scale (WAIS). However, this may be due to the inclusion of all deletions regardless of Page 4 of 38 A c c e p t e d M a n u s c r i p t 4 frequency and could explain the discrepancy between their findings and the findings of Yeo et al [4].…”
mentioning
confidence: 95%